La investigación formativa como estrategia pedagógica para la construcción del conocimiento. Una mirada desde las políticas, los actores, las prácticas y los discursos - Granja Escobar, Luis Carlos (Universidad Santiago de Cali, 2017)
Formative Research is related to different areas that characterize it and define it in pedagogical, curricular, didactic and sociocultural aspects. This theme was developed within the framework of the theoretical-methodological mo-del, based on the policies, actors, practices, discourses and agencies that in-fluence Education for Research. Therefore, each of the following sections are linked to the Formative Research, in this order: